Types of building defects in Hotel Perdana Kota Bharu, Kelantan / Nik Luqman Hakim Mohd Hanipa - Mohd Hanipa, Nik Luqman Hakim (2016)
This report focuses on the building structure defects in Hotel Perdana Kota Bharu buildings. There are several building defects commonly found in Hotel Perdana buildings. In fact, building defects are becoming ordinary phenomena in the construction industry which results in negative impacts on hotels, in the means of building performance, health and safety aspects. Thus, a study is planned to identify the common building defects faced by hotel perdana buildings in Kelantan, Malaysia. Then, a thorough inspection is conducted and the respective defects are recorded with the aid of photographic. Besides, This report is divided into a few chapter which is company background, literature review, case study and conclusion & recommendation. In addition, the causes and remedial work of defect also been discussed in this report.